The Application of Electrolysis Method to Reduce Ammonia Content in Liquid Waste of Tofu. (April 2018) - Prabowo, S; Nurlaili,; Muflihah,; Tindangen, R A; Sukemi,
Abstract: Ammonia (NH3 ) is known as an important chemical in industrial sector. It is also known as harmful pollutant. Ammonia is a weak base, a gas in room temperature and has 330°C of BP. The aims of research were to investigate the effect of voltage (4 to 12 volt), time (1 to 30 min.), concentration of ammonia (0.01 to 0.05 M) and potassium hydroxide concentration on the ammonia content in aqueous solution by using electrolysis method with platinum as electrodes. The ammonia content was analysed by using UV-Vis spectrophotometer. The result showed that an increment in the voltage, time and potassium hydroxide concentration could increase the amount of converted ammonia. The optimum condition to reduce the ammonia content by using electrolysis method was 10 V of electrical voltage, 25 min. of electrolysis time and 0.04 M of potassium hydroxide concentration. At the optimum condition, the electrolysis method could decrease 81.13% of ammonia content in liquid waste of tofu.